Efficiency in the Spanish penal system: with special reference to the plea bargaining model - Claudio Javier González Guarda (Revista Brasileira de Direito Processual Penal, 2021)
The present work describes the way in which some efficient logics have been positioned in the Spanish penal system. With this objective, a systematic review of the political-criminal literature on the matter has been carried out. Likewise, the instructions of the Attorney General’s Office, various reports on the New Judicial Office (NOJ), judicial statistics and preliminary draft of criminal procedure codes (2011, 2012 and 2020), among other pertinent information, have been examined. In this way we determine three areas to observe this phenomenon. 1) In the respective political-criminal literature; 2) In the attempt to implement an “organic managerialism” manifested in the so-called New Judicial Office; and 3) In the justice system negotiated in Spain, especially in the plea bargaining model. We conclude that: a) Despite the few studies on management / efficiency in Spain, its penetration is undoubted. Certainly different from other contexts (Anglo-American and Latin-American); b) The consolidation of an efficient model of accelerationist features of criminal justice is configured not only by legal factors, but also by socio-economic, technological and criminological elements; c) Its main manifestation is observed in the rapid procedures and in the plea bargaining model (way of ending the litigation in 70% of ordinary cases and in 90% of rapid trials); d) The attempts to transform the entire organizational dimension of criminal justice have not materialized.